Thiopurine methyltransferase polymorphisms in children with acute lymphoblastic leukemia - Linga, Vijay Gandhi (Indian J Med Paediatr Oncol, 2014)
INTRODUCTION: Acute lymphoblastic leukemia (ALL) is the most common malignancy in children. 6-mercaptopurine (6-MP) and methotrexate are backbone drugs for maintenance phase of treatment. Purine Analogs 6-MP/6-thioguanine/azathiopurine are metabolized to its inactive form by the enzyme thiopurine methyltransferase (TPMT). Ninety percent of the population harbor wild type on both alleles (TPMT wild/wild), 10% are heterozygous, that is, one allele is mutant (TPMT wild/mutant) and 0.3% are homozygous, that is, both allele are mutant (TPMT mutant/mutant). In heterozygous and homozygous variant, activity of enzyme is low, leading to a higher incidence of toxicity (myelosuppression). AIM: The primary objective was to access the polymorphism of the enzyme, TPMT, in Children with ALL. Secondary objective was to correlate TPMT genotype with 6-MP toxicities. MATERIALS AND METHODS: Seventy-two children with newly diagnosed ALL during first maintenance phase were serially enrolled after obtaining consent. Five ml of peripheral blood was drawn and DNA extracted. TPMT 2 polymorphisms were performed using Allele specific polymerase chain reaction (PCR) and TPMT 3B and 3C are performed by PCR-restriction fragment length polymorphism. RESULTS: Sixty-nine children of 72 (95.8%) were wild for TPMT polymorphism and 3 (4.2%) were heterozygous for TPMT. Among the heterozygous variant one each (33.3%) were heterozygous for 2A, 3A, 3C. Febrile neutropenia was the most common toxicity in both wild and heterozygous group. CONCLUSION: The frequency of TPMT polymorphisms in children with ALL is 4.2%. Heterozygous variant is this study are one each (33%) of 2A, 3A, 3C.